Fathering Agency Staff Members’ Perspectives on Domestic Violence Perpetration - Peter F. Cronholm MD, MSCE; Willie Ellison MSW, LSW; Silvana Mazzella BSW, MA GUS; Marcy Witherspoon MSW, LSW; Joy Bowman Lim MSW, LSW; Tony Lapp LCSW; Gilbert Coleman BBA (American Journal of Men's Health, 2011)
Purpose: To describe the perspectives of fathering staff regarding domestic violence (DV) perpetration. Materials and methods: A cross-sectional survey of 85 fathering staff members was conducted to identify behaviors and barriers regarding inquiry about DV perpetration. Results: Almost half (47.1%) of the surveyed staff reported never having identified DV perpetration. Routine inquiry was less likely if staff perceived low prevalence rates among their clients (odds ratio [OR] = 0.11, p = .001), did not have standard ways of asking (OR = 0.11, p < .001), or if they had never identified family violence before (OR = 0.07, p < .001). Increased years as a provider (OR = 6.62, p = .001) and DV training (OR = 7.29, p = .003) increased rates of DV perpetration inquiry. Conclusions: Staff of fathering agencies do not routinely screen for DV perpetration likely due to the interplay between individual and agency-level barriers. Appropriate training interventions can address identified barriers.